1973
DOI: 10.1111/j.1540-4560.1973.tb00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Mobility among Three Generations of Japanese Americans1

Abstract: Data from a three generational survey of Japanese Americans indicate that the occupational and educational attainments of the first generation (Issei) are reflected in the achievements of the second and third generations. Findings suggest that two different currents flow in the Japanese American community, one relatively traditional, the other more assimilationist. It is expected that only assimilationists will survive-but in a modified fashion. The majority of the Sansei queried indicate an interest in Japane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 3 publications
1
14
0
Order By: Relevance
“…It seems reasonable to consider the atti tudes through the two types of organization. These observations were congruent with the study of Levine and Montero (1973) which suggested two different Sansei streams, paralleling the choices of the previous generations, that is, one is more traditional, following traditions of the ethnic cultures, while the other is accultur ationist. Practically, these different progressions were revealed in the statistics of survey results, and features of acculturation might be confirmed.…”
Section: Discussionsupporting
confidence: 75%
“…It seems reasonable to consider the atti tudes through the two types of organization. These observations were congruent with the study of Levine and Montero (1973) which suggested two different Sansei streams, paralleling the choices of the previous generations, that is, one is more traditional, following traditions of the ethnic cultures, while the other is accultur ationist. Practically, these different progressions were revealed in the statistics of survey results, and features of acculturation might be confirmed.…”
Section: Discussionsupporting
confidence: 75%
“…For example, despite often having college degrees in an era when such credentials were relatively rare, many secondgeneration Japanese American (i.e., Nisei) men would not be employed by white-owned companies (Ichihashi 1932, Thomas 1952. Large proportions of Nisei men therefore ended up working as gardeners, grocers, and workers in related lower-status occupations (Broom & Riemer 1949, Levine & Montero 1973, Kitano 1976, Chin 2005. Controlling for occupation in a regression model of earnings during this period underestimates the total disadvantage of minority status in the labor market because these low levels of occupational attainment at least partly derive from racial discrimination in the first place.…”
Section: Pums: Public-use Microdata Sample From the Us Censusmentioning
confidence: 97%
“…mese case. gration experience: the historically documented early Asian (Chinese and Japanese) immigration experience (Ichihashi, 1932;Kitano, 1976;Levine and Montero, 1973;Lyman, 1974;Miyamoto, 1939) compared with what is considered here to be the unique Vietnamese experience of spontaneous international migration. This third distinctive pattern shall be referred to as the Spontaneous International Migration (S.I.M.)…”
Section: Receipt Of Federal Assistancementioning
confidence: 94%